The effect of difficult letters on primary school students' writing ability - Jee, Kai Yien (Universiti Malaysia Sarawak, UNIMAS, 2014)
This study examined the effect of difficult letters on primary school students’ writing ability. A sample of 150 and 162 Primary Two students, in study 1 and study 2, respectively, were examined. This was a quantitative study where descriptive and inferential statistics were used to analyze the data. Four samples of writing (i.e., writing full names, capital letters, small letters, and copying words) were collected. The students exhibited a range of proficiency in their ability to write their full names, capital letters, small letters, and to copy words. Capital letters G, M, W, and Y and small letters g, j, q, k,and f were difficult letters. In study 1, students with higher percentage of difficult letters in their names had significantly lower name writing scores. Also, in study 1, students with higher difficulties in writing small letter had significantly lower scores in copying the word queen . This study shed light on the importance of transcription (i.e., the students’ ability to write the dictated letters) as some letters are difficult for the students to write. Implications of the findings on handwriting instruction and intervention are discussed.